The Effects of University-Industry Collaboration in R D on the Growth of Innovative Companies - Hülya Keskin Çalışkan; Gamze Sart (Üniversite Araştırmaları Dergisi)
Technological changes and innovations based on the Research and Development (R amp;D) are vital role to increase the competition level and economic growth for both firms and countries. For this reason, university-industry collaboration in R amp;D has important role for the growth of innovative companies. In this context, main of this study is the effects of university-industry collaboration in R amp;D on the growth of innovative companies. According to the empirical results, the mean of growth innovative companies increases as the level University industry collaboration in RD increases. As a result, it is critical to strengthen University industry collaboration in RD in order to increase the sustainable competition level and economic growth for both firms and countries.